Further experiments in dispersal of phytoplankton by birds - Atkinson, Kathleen M (Wildfowl, 1971)
Lycopodium spores fed to Mallard Anas platyrhynchos as a marker were found in the faeces from 1-51 hours after feeding. Five species of planktonic diatom and one Cyanophyte were fed to Mallard and their cells found in the faeces. Only Melosira sp., which was found in very large numbers in one culture, had passed through the gut in a viable condition.